ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN TERHADAP SAYURAN HIDROPONIK DI UD. ACEH HIDROPONIK KECAMATAN KARANG BARU KABUPATEN ACEH TAMIANG - Ahmad Nazri Dwi Nugrah; Rozalina Rozalina; Thursina Mahyuddin (Sekolah Tinggi Pariwisata Mataram, 2022)
This research was conducted at UD. Aceh Hydroponics, Medang Ara Village, Karang Baru District, Aceh Tamiang Regency. This study aims to determine the factors that influence consumer buying interest in hydroponic vegetables at UD. Aceh Hidroponik, Karang Baru District, Aceh Tamiang Regency. The results obtained are the Quality Variable (X1) does not have a significant effect on buying interest in hydroponic vegetables at UD. Aceh Hydroponics, Karang Baru District, Aceh Tamiang Regency.. Price variable (X2) has a significant influence on buying interest in hydroponic vegetables at UD. Aceh Hydroponics, Karang Baru District, Aceh Tamiang Regency. Distribution variable (X3) does not have a significant effect on buying interest in hydroponic vegetables at UD. Aceh Hydroponics, Karang Baru District, Aceh Tamiang Regency. Promotion variable (X4) has a significant effect on buying interest in hydroponic vegetables at UD. Aceh Hydroponics, Karang Baru District, Aceh Tamiang Regency.